Evaluation of Household Finance Management Effectiveness in the Biggest Polish Cities - Musiał, Marta (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main objective of the paper is to evaluate household finance management effectiveness in the biggest Polish cities. As part of the conceptualization study, the following specific objectives are set: adaptation of effectiveness approaches in relation to households functioning and a proposition of household finance management effectiveness evaluation model. In addition, an attempt has been made to verify the following hypothesis (H): Polish households are characterized by low financial management effectiveness, which is a result of low level of financial literacy, as well as lack of financial control. Within the research framework, the following research methods have been used: a critical analysis of the literature on the subject, a document research method, diagnostic questionnaire method, comparative research method and statistical methods.